2019
DOI: 10.1038/s41390-019-0359-y
|View full text |Cite
|
Sign up to set email alerts
|

Origins of neonatal leptin deficiency in preterm infants

Abstract: Background: Cord blood leptin increases with advancing gestation. Preterm delivery leads to premature separation from the maternal and placental leptin source predisposing infants to postnatal leptin deficiency, but this has not been fully described. Method: Blood leptin levels were measured for infants born before 33 weeks gestation daily for the first 2 days, then weekly until 36 weeks postmenstrual age (PMA). Cord blood was obtained to provide gestational age (GA)-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 49 publications
(62 reference statements)
2
20
0
Order By: Relevance
“…9 Newborns with low birth weight (preterm and SGA) have less body fat and lower leptin levels than those with adequate birth weight. 8,30 In this study, the median leptin concentration was 2.0 ng/ml. These values are in agreement with a study carried out with 317 healthy infants and younger than 18 months, but who were born AGA; the authors observed a median and 90th percentile of leptin levels between 6 and 12 months of age of 1.44 ng/ml and 5.18 ng/ml, respectively.…”
Section: Discussionmentioning
confidence: 56%
“…9 Newborns with low birth weight (preterm and SGA) have less body fat and lower leptin levels than those with adequate birth weight. 8,30 In this study, the median leptin concentration was 2.0 ng/ml. These values are in agreement with a study carried out with 317 healthy infants and younger than 18 months, but who were born AGA; the authors observed a median and 90th percentile of leptin levels between 6 and 12 months of age of 1.44 ng/ml and 5.18 ng/ml, respectively.…”
Section: Discussionmentioning
confidence: 56%
“…18 Leptin is a typical adipokine secreted by adipocytes and research has shown that the leptin level is decreased in preterm infants. 19 All of these findings suggest that lipid metabolism is involved in the pathogenesis of preterm birth. 20 The STRING diagram ( Figure 2) shows that apoA-II interacts with plasma kallikrein, coagulation factor XIII A chain, coagulation factor XII, complement component C8 alpha chain and other important coagulation and immune factors involved in preterm birth.…”
Section: Discussionmentioning
confidence: 99%
“…Since the preterm delivery leads to a premature separation from the maternal/placental leptin source, the infant is predisposed to postnatal hormone deficiency, enhanced by the lack of adipose tissue, which increases during the last three months of fetal life. Thus, leptin in the breastmilk could be a substitute source for neonates, particularly those born preterm [ 26 ]. In our study, leptin concentrations in maternal milk resulted in a similar small amount in each group, lower than the corresponding levels in maternal plasma and CB.…”
Section: Discussionmentioning
confidence: 99%